Ein neuer Versuch zum ägyptischen Ausfall von k (nebst einem Anhang zum möglichen Lautwandel zwischen k und i) - Bojowald, Stefan.
The present contribution is devoted to the study of the loss of k in the Egyptian language. The phenomenon has been discussed sporadically in previous research. The number of examples is enhanced here significantly. The material consists of writings of single words on the one hand, and puns on the other. In an appendix, the probability of the phonetic change between k and i is widened.